Genome instability methods and protocols - Muzi-Falconi, Marco; Brown, Grant W. (Methods in Molecular Biology, 2018)
This volume presents forty-two methods and protocols to analyze diverse aspects of genome instability. Chapters detail mutagenesis and repair, methods to quantify and analyze the properties of DNA double-strand breaks, profile replication, replication proteins strand-specifically, genome instability, fluorescence microscopic techniques, and genomic and proteomic approaches. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Genome Instability: Methods and Protocols aims to provide a comprehensive resource for the discovery and analysis of the proteins and pathways that are critical for stable maintenance of the genome